Identification of Employee Core Capability Through Knowledge Management (Study at Plant Conservation Botanic Gardens, Indonesian Institute of Science) - Novia Andriani Mahardheny; Mujibur Rahman Khairul Muluk; Endah Setyowati (JPAS (Journal of Public Administration Studies), 2022)
The ability of employees known as employee competency is one of the strengths for the organization. Recently the concept of core competency has shifted to a core capability that is an organizational ownership that is different from the others. The aim of the research is to identify the core capability of employees at Plant Conservation Botanic Gardens through knowledge creating activities. This type of research uses a description method with a qualitative approach. The results showed that in the Plant Conservation Botanic Gardens has carried out a process of knowledge creating activities consisting of consisting of joint problem solving, integration of new tools and methodologies, experimentation and prototype preparation, and absorption of knowledge from outside the organization so that core capability from skill dimensions and knowledge.